Self-Esteem And Adversity Quotient To Increase Learning Independence - Djunaidah, Siti; Matulesy, Andik; Rini , Rr Amanda Pasca (International Journal of Research in Counseling, 2023)
This study aims to determine whether there is a relationship between Self-Esteem and Advertasy Quetient with learning independence.  In the research for class VIII students  whose population was 284 students, the number of samples taken was 126 students. From the results of the study, there was a relationship between Self-Esteem and Adversity Quotient with learning independence in Madrasah Tsanawiyah Negri 3 Surabaya students "accepted", data analysis used  multiple linear regression analysis using SPSS version 20.00 The results of calculating the value of F = 3.226 with sig/p = 0.043 (p <0.05) mean that there is a very significant relationship simultaneously between Self-Esteem and Advertasy Quetion with learning independence Keywords:  Self-Esteem Adversity Quotient, learning independence